The birthday pet - Javernick, Ellen; O'Malley, Kevin, 1961- (Tarrytown, NY : Marshall Cavendish Children, 2009)
Danny can have a pet for his birthday and he knows exactly what he wants, but the other members of his family think differently.
Kirkus Review.
1.7
K-3
Keywords: Birthdays -- Juvenile fiction; Pets -- Juvenile fiction; Turtles -- Juvenile fiction; Birthdays -- Fiction; Pets -- Fiction; Stories in rhyme; Turtles -- Fiction; Birthdays -- Fiction; Pets -- Fiction; Stories in rhyme; Turtles -- Fiction